Quarantine-related traumatic stress, views, and experiences during the first wave of Coronavirus pandemic: A mixed-methods study among adults in Saudi Arabia. - Halah Bin Helayel; Anwar Ahmed; Syed Khabir Ahmed; Abeer Ahmad; Ruhi Khan; Samar A Al-Swailem (PLoS ONE, 2022)
Purpose Mental health is a significant problem following exposure to a traumatic event. This study aimed to examine quarantine-related experiences, traumatic stress, and coping strategies among adults quarantined in Saudi Arabia due to coronavirus disease 2019 (COVID-19) exposure or travel history. Methods Individuals aged ≥ 18 years who were quarantined in Saudi Arabia due to COVID-19 exposure or travel history were included. We used a sequential mixed methods design, using an online survey followed by in-depth individual telephonic interviews. The Impact of Event Scale-Revised (IES-R) was used to measure post-traumatic stress disorder (PTSD) symptoms after the quarantine. To identify factors associated with significant symptoms (IES-R score ≥ 33), prevalence ratios (PR) with 95% confidence intervals were computed using Poisson regression with robust error variance. In the next phase, a subset of the participants (n = 26) were interviewed to elicit their quarantine-related experiences and coping responses. Major themes and subthemes were identified. Results Of the 111 adults who completed the survey, 32 (28.8% [95% CI, 21.1-38.0%]) had significant PTSD symptoms (IES-R score ≥ 33) and 27 (24.3% [95% CI, 17.2-33.3%]) had severe symptoms (IES-R score > 37). Marital status was the only variable that was significantly associated with significant PTSD symptoms (P = 0.028). Significant symptoms were twice as prevalent in married adults than among other marital groups (PR 2.00, 95% CI, 1.08-3.72). Participants reported negative emotions such as overwhelming fear, helplessness, anxiety, and disgust. Participants utilized both problem-centered coping (e.g., use of social support) and emotion-centered coping (e.g., use of positive diversionary activities) during the quarantine period. Conclusion PTSD symptoms were present in one out of every four quarantined persons. The quarantine experience is viewed negatively. These findings highlight the need for increased awareness about stress-related disorders among quarantined individuals. Efforts are needed to detect and manage these symptoms early while making the quarantine experience more satisfying for the involved individuals and groups.